Polyurethane Nanofiber Membranes for Waste Water Treatment by Membrane Distillation - T. Jiříček; M. Komárek; T. Lederer (Journal of Nanotechnology)
Self-sustained electrospun polyurethane nanofiber membranes were manufactured and tested on a direct-contact membrane distillation unit in an effort to find the optimum membrane thickness to maximize flux rate and minimize heat losses across the membrane. Also salt retention and flux at high salinities up to 100 g kg−1 were evaluated. Even though the complex structure of nanofiber layers has extreme specific surface and porosity, membrane performance was surprisingly predictable; the highest flux was achieved with the thinnest membranes and the best energy efficiency was achieved with the thickest membranes. All membranes had salt retention above 99%. Nanotechnology offers the potential to find modern solutions for desalination of waste waters, by introducing new materials with revolutionary properties, but new membranes must be developed according to the target application.